(untitled) (Raparin Journal of Humanities (RJH), 2024)
Western writers have appreciated the role of women who had a crucial position in their own societies. This perspective is related to the nature of their society, which the west have always valued women. They believe in the significant role that women could play in society and influence on revolutions and events in different eras and circumstances. The Aylul Revolution of Iraqi Kurds, as a turning point in their contemporary history, has been a matter of debate to the Westerners. They visited the areas of Iraqi Kurdistan which had been liberated by the revolution and paid attention to the role that people from different communities, played, including women. Women had been delt as significant members of society. Thus, the Westerners have expressed their views on women from different aspects of life. While that times were very tough for women and there were lots of obstacles and challenges, they complemented and helped men during the revolution.